Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention Pada Karyawan di Perusahaan Konstruksi Bangunan - Aisyah Nur Jannavi; Kristiana Sri Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of job satisfaction and job stress on turnover intention in employees of one of the building construction companies in Batam city. The research method used is quantitative. The population in this study were all employees at one of the building construction companies in Batam city, which amounted to 25 people. Sample determination using saturated sample technique where the entire population is sampled. Data collection is done by distributing questionnaires. After the instrument test and classical assumption test are carried out, then data analysis is carried out using multiple linear regression analysis, determination, t test, and F test. The results of the analysis show that there is no effect of job satisfaction (X1) on turnover intention (Y) in employees of building construction companies. Job stress (X2) has no effect on turnover intention (Y) in employees of building construction companies. Job satisfaction (X1) and job stress (X2) together have no effect on turnover intention (Y) in employees of building construction companies.